Industrial hemp biomass negatively affected by herbicide drift from corn and soybean herbicides - Milos Zaric; Bruno Canella Vieira; Barbara Houston; Guilherme Sousa Alves; Sam E. Wortman; Julie Peterson; Greg R. Kruger (Scientific Reports)
Abstract The establishment of industrial hemp (Cannabis sativa L.) fields near row crops has raised concerns about the potential adverse effects of herbicide drift on hemp production. This study examined hemp susceptibility to drift of herbicides registered for use in corn and/or soybeans. Herbicide solutions (2,4-D, dicamba, glufosinate, glyphosate, imazethapyr, lactofen, mesotrione) were applied separately in the wind tunnel (3.6 m s−1 airspeed), simulating drift scenarios, with conventional TP95015EVS (TP) and air inclusion AI95015EVS (AI) flat fan nozzles calibrated to deliver 140 L ha−1 carrier volume at 230 kPa. Mylar cards and hemp plants (20–25 cm tall) were placed downwind up to 12 m. Spray deposition from mylar cards was quantified using fluorometry and hemp biomass was collected 21 post application. Results indicated the nozzle design influenced downwind deposition; 5% of spray deposits from the TP nozzle reached 5.9 m downwind versus 2.0 m for the AI nozzle. Glyphosate, glufosinate, and mesotrione caused the highest biomass reductions, with 50% reductions observed at 19.3 (inferred), 8.7, and 9.3 m downwind for TP nozzle, and 4.1, 4.0, and 2.9 m for AI nozzle. These findings suggest herbicide applications at airspeeds of 3.6 m s−1 or greater present a risk to nearby hemp fields.